Production method and optimization of puffing tofu skin snack using home microwave oven - Sompong, Ratanachai; Songsermpong, Sirichai (Agriculture and Natural Resources, 2022)
Importance of the work: The microwave puffing method can produce a non-fried tofu skin snack to replace the fried snack. Objectives: To investigate the production method and optimization of puffing a tofu skin snack using response surface methodology (Box-Behnken technique). Materials & Methods: The sample conditions were optimized based on the initial moisture content (IMC), microwave power (MWP) and puffing time (PT). The tofu skin samples were pre-dried at 40 °C using a hot-air oven to have different initial moisture content conditions. Then, the samples were puffed in a home microwave oven. Results: The results indicated that the IMC and MWP were the most important parameters affecting all responses, followed by the PT. The optimum conditions for puffing tofu skin in a microwave oven were an IMC of 55%, an MWP of 1,071 W and a PT of 111 s, producing a 0.836 desirability index value. Conditions involving an IMC value outside the range 56.5–57%, an MWP value that lower than 1,200 W or a PT value that lower than 120 s resulted in a reduced expansion ratio and reduced the crispness but increased the hardness. However, lower IMC and higher MWP values resulted in decreased lightness, whereas the redness and yellowness increased. In addition, the moisture content after puffing was inversely proportional to the expansion ratio. Main finding: This knowledge can be used to produce healthy snacks based on a novel method with rapid heating, high temperature and a short processing time that did not cause a loss of nutritional food value.